2022
DOI: 10.1111/eea.13244
|View full text |Cite
|
Sign up to set email alerts
|

Review of entomopathogenic fungi and nematodes as biological control agents of tephritid fruit flies: current status and a future vision

Abstract: Several fruit fly species (Diptera: Tephritidae) are invasive pests that damage the quality of fruits in horticultural crops and cause significant value losses worldwide.Management of fruit flies mainly depends on conventional insecticides. Unfortunately, the application of synthetic insecticides has caused environmental pollution, risks for humans and animals, and development of resistance. Furthermore, controlling fruit flies by applying synthetic insecticides is challenging because fruit containing third in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 152 publications
0
10
0
Order By: Relevance
“…Moreover, Usman et al (2021) and Wakil et al (2022) found that B. dorsalis pupae were more susceptible than larvae, which does not align with our current findings. The contrasting results may be due to differences between the strains of B. bassiana , the method of application, and the age of the pupae ( Rizvi et al, 2009 ; Beris et al, 2013 ; Gul et al, 2015 ; Soliman et al, 2020 ; Shaurub, 2022 ). We focused on one- to two-day-old pupae, whereas previous research showed that the older the pupae, the less susceptible they are to EPF ( Poprawski et al, 1985 ; Hussein et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Usman et al (2021) and Wakil et al (2022) found that B. dorsalis pupae were more susceptible than larvae, which does not align with our current findings. The contrasting results may be due to differences between the strains of B. bassiana , the method of application, and the age of the pupae ( Rizvi et al, 2009 ; Beris et al, 2013 ; Gul et al, 2015 ; Soliman et al, 2020 ; Shaurub, 2022 ). We focused on one- to two-day-old pupae, whereas previous research showed that the older the pupae, the less susceptible they are to EPF ( Poprawski et al, 1985 ; Hussein et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature and humidity are the most important environmental factors affecting the growth and virulence of B. bassiana ( Dorschner et al, 1991 ; Shaurub, 2022 ). Our results are consistent with Pan et al (2008) , who found that 25°C and 90–100% RH were the optimum temperature and humidity for spore germination and colony growth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to performance, factors including cost, availability, compatibility within integrated strategies and alternative options for organic growers will ultimately determine the extent to which nematodes are used against Dipteran insect pests [72, [78][79][80]. To make entomopathogenic nematodes more successful, realistic strategies through genetic engineering [81], IPM programs, and new delivery systems and/or training programs to overcome their inherent cost, formulation instability, and limited field efficacy toward the Dipteran pests are needed [82,83]…”
Section: Discussionmentioning
confidence: 99%
“…EPNs have been evaluated in combination with insecticides, biocontrol agents, and parasitoids to increase their efficacy against insect pests [ 49 , 99 , 100 , 101 , 102 , 103 ]. Several factors can influence the interaction between EPF and EPNs, such as the species and strains of EPF and EPNs, the target insect host, application parameters, and environmental conditions [ 49 , 103 , 104 , 105 , 106 , 107 ]. The combined use of two biocontrol agents can result in diverse effects on the mortality of the target pests [ 49 , 53 , 89 , 108 , 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%